2011
DOI: 10.4161/mabs.3.6.17955
|View full text |Cite
|
Sign up to set email alerts
|

Rational identification of an optimal antibody mixture for targeting the epidermal growth factor receptor

Abstract: (2011) Rational identification of an optimal antibody mixture for targeting the epidermal growth factor receptor, mAbs, 3:6, 584-595,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 34 publications
1
91
0
Order By: Relevance
“…Furthermore, the activation of EGFR mAb-triggered MoAs may be improved by combinations of noncompetitive EGFR mAbs to artificially enhance the Ag density on the tumor cell surface. Thus, combinations of EGFR mAbs were demonstrated to enhance CDC (20), as well as EGFR internalization (49), a concept that is currently under evaluation in clinical studies. Alternatively, Fc engineering approaches improved Fc-mediated MoAs, such as ADCC or CDC, against target cells with low levels of EGFR expression (21, 50).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the activation of EGFR mAb-triggered MoAs may be improved by combinations of noncompetitive EGFR mAbs to artificially enhance the Ag density on the tumor cell surface. Thus, combinations of EGFR mAbs were demonstrated to enhance CDC (20), as well as EGFR internalization (49), a concept that is currently under evaluation in clinical studies. Alternatively, Fc engineering approaches improved Fc-mediated MoAs, such as ADCC or CDC, against target cells with low levels of EGFR expression (21, 50).…”
Section: Discussionmentioning
confidence: 99%
“…Spleens were recovered and macerated through a 74-mm cell strainer (Corning) generating single-cell suspensions. Antibodies specific for IGF1R were cloned using the murine Symplex technology, as previously described by Koefoed and colleagues (30). The two anti-EGFR antibodies (1565, 1277) and the two anti-HER3 antibodies (5038, 5082) are described by Koefoed and colleagues.…”
Section: Production Of Antibodies and Antibody Mixturesmentioning
confidence: 99%
“…The two anti-EGFR antibodies (1565, 1277) and the two anti-HER3 antibodies (5038, 5082) are described by Koefoed and colleagues. (30) and Jacobsen and colleagues (35). Antibody mixtures were generated freshly prior to the individual experiments and mixed in ratios of 1:1 or 1:1:1 (w/w).…”
Section: Production Of Antibodies and Antibody Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique feature of Sym004 is its ability to mediate rapid EGFR internalization and subsequent degradation of internalized receptors via EGFR cross-linking ( 17,18 ). Preclinical studies with Sym004 showed both superior induction of tumor regression as compared with other EGFR-targeting antibodies and antitumor activity in models of acquired cetuximab resistance ( 7 , 17 ).…”
Section: Introductionmentioning
confidence: 99%